Accounting for sustainability: a case study in a vehicle dealer in the north region of Rio Grande do Sul state - Andriolli, Elaine Marisa; Ávila, Silvia Regina da Silva; Sandri, Alessandra Wolf; Felten, Amanda de Castro (Revista de Administração da UFSM, 2016)
The term sustainability is used to ensure that human activities are carried out in order not to compromise the future. In this wider context, also arises, environmental accounting as an innovative tool for sustainable management by providing information demonstrating solutions to prevent or reduce environmental damage. This work aims to highlight the importance of environmental accounting, checking the concessionaire Netherlands Vehicles Palmeira of Missions, Rio Grande do Sul, holds records of environmental accounting, specifically in the financial statements. The data used for this study were obtained through case study and on-site observation including analysis of the financial statements of the years 2012 to 2014, provided by the car dealership studied and through a semi-structured interview descriptive exploratory nature, in November 2014, with the manager and owner of the company. As the results showed that the company performs some environmental practices, however, does not have the environmental accounting